Integrity of the Halal Supply Chain Conceptual Framework - Ahmad Hidayat Sutawidjaya; Lenny C Nawangsari (International Journal of Supply Chain Management, 2020)
Purposes- The development of halal has become life style for the majority of muslims. Consumers of muslims in the whole world must ensure that the food that they eat in accordance with requirements Islamic law. This is also strategy for the adoption of catering to the supply chain. This study attempts to create designs over supply chain in catering company in Jakarta. The purpose of this research is to produce new paradigm in halal supply chain catering industry. Design/methodology–This study presents the results of discussions about the halal supply chain framework at catering companies in Jakarta through a triangulation approach and supported by literature. Research limitations / implications– This research only focuses on Diamond catering companies in Jakarta. Loyal consumers provide an evaluation of the services provided by the company.